Enhancing the Knowledge and Skill of PKK and Karang Taruna Cadres in The Innovation of Mangosteen Fruit Products - Suciati Suciati; Wiwied Ekasari; Andang Miatmoko; Neny Purwitasari; Lidya Tumewu; Yanu Andhiarto; Fatin Fadhilah Hasib; Tri Widiandani; Kholis Amalia Nofianti (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: The current community service activities aim to provide knowledge and skills related to mangosteen and its processed products to the Songgon Village community Method: Transfer of knowledge and skill by lecturing and practice. Pre and post-tests were carried out to evaluate the participants’ knowledge before and after the workshop. Practical Applications: The knowledge and skill gained by PKK and Karang Taruna cadres in this workshop can be implemented in daily life. The participants learned how to make innovative products from mangosteen fruit so that it can be produced commercially. Thus, in the long term is expected to increase the income of Songgon Village Community. Conclusion: The results showed the participants' enthusiasm to participate in this activity, and the pre and post-tests demonstrated increased knowledge and skills. The next step requires intensive support for the Songgon Village community so that their products can be distributed commercially and provide economic benefits.